2019
DOI: 10.1002/adma.201900871
|View full text |Cite
|
Sign up to set email alerts
|

Addition of the Lewis Acid Zn(C6F5)2 Enables Organic Transistors with a Maximum Hole Mobility in Excess of 20 cm2 V−1 s−1

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201900871.Incorporating the molecular organic Lewis acid tris(pentafluorophenyl)borane [B(C 6 F 5 ) 3 ] into organic semiconductors has shown remarkable promise in recent years for controlling the operating characteristics and performance of various opto/electronic devices, including, light-emitting diodes, solar cells, and organic thin-film transistors (OTFTs). Despite the demonstrated potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 56 publications
1
78
0
Order By: Relevance
“…The intentional introduction of molecular dopants has been used extensively to alter the charge transport properties of organic semiconductors, particularly in the area of organic thin‐film transistors (OTFTs) for which some of the highest carrier mobilities have been achieved via this method 6–9. Molecular doping relies on charge transfer interaction(s) between the dopant and the host semiconductor, which ultimately results in formation of free carriers 10,11.…”
Section: Summary Of Operating Parameters Of Solar Cells Based On Pm6:mentioning
confidence: 99%
See 2 more Smart Citations
“…The intentional introduction of molecular dopants has been used extensively to alter the charge transport properties of organic semiconductors, particularly in the area of organic thin‐film transistors (OTFTs) for which some of the highest carrier mobilities have been achieved via this method 6–9. Molecular doping relies on charge transfer interaction(s) between the dopant and the host semiconductor, which ultimately results in formation of free carriers 10,11.…”
Section: Summary Of Operating Parameters Of Solar Cells Based On Pm6:mentioning
confidence: 99%
“…Molecular doping relies on charge transfer interaction(s) between the dopant and the host semiconductor, which ultimately results in formation of free carriers 10,11. Recent studies have shown that molecular doping may, under certain conditions, induce multiple synergistic effects including microstructural changes to the host semiconductor and drastic improvement in charge carrier transport 6,8,9. These effects were shown to be the result of the dual functionality of the molecular dopants, acting both as electronic dopants and microstructure modifying agents.…”
Section: Summary Of Operating Parameters Of Solar Cells Based On Pm6:mentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm that PCDTPT was doped by TrTPFB, electron spin resonance (ESR) measurements were performed at room temperature. As seen in Figure 2b, even the 1 wt% TrTPFB doped sample shows strong paramagnetic signals, demonstrating the existence of unpaired electrons 34. In contrast, PCDTPT and pure TrTPFB (see Figure S2a, Supporting Information) samples were observed without paramagnetic signals.…”
mentioning
confidence: 92%
“…These dopants either have a very deep lowest unoccupied molecule orbitals (LUMO) (p‐dopants) or a very shallow highest occupied molecule orbitals (HOMO) (n‐dopants), and can effectively dope the semiconductors by forming ion‐pairs or charge transfer complex 32. In the past few years, the dopants and doping techniques for organic semiconductors have been progressed tremendously, with novel dopants like Lewis acid (for p‐doing) and Lewis base (for n‐doping) demonstrating significant doping effects for improving performance in OFETs or OPVs 33–36. However, these new doping techniques have not been fully implemented for OTE applications, and therefore it is worth exploring novel dopants to further enhance the thermoelectric performance of OTEs.…”
mentioning
confidence: 99%